Assessment of Computer Literacy Skills and their Utilization in the Teaching of Basic Science in Junior Secondary Schools in Imo State - Ettu, Theresa Ucheoma.; Ezeribe, Scholastica Ngozi; Ekechukwu, Leona Eucheria; Anyanwu, Julius Okechukwu; Okoroji, Lazarus (American Journal of Education and Learning, 2016)
Computer resource has been widely seen as a sin-quo-non to teaching in various subjects world-wide. Prior to preliminary investigations of this, it was found out that the effect of computer utilization has not been properly felt in most junior secondary schools in Nigeria. This study investigated the possession and utilization of computer literacy skills by Basic Science teachers in Owerri Education Zone I & II of Imo State. The sample consists of 90 Basic Science teachers who were drawn from a population of 135 Basic Science teachers from the area of study: Proportionate random sampling technique was used to draw 90 teachers from 11 local government areas in the zones. Relevant data were collected from the sample using a questionnaire titled “Basic Science Teachers’ Questionnaire on Computer Literacy Skills”. Test and re-test method was used to find out reliability co-efficient within an interval of two weeks with 10 subjects who did not form part of the final samples. The four research questions posed were answered with mean and standard deviation while the four hypotheses formulated were tested with t-test of independent mean. The results of the analysis among other things showed that gender does not significantly influence literacy skills by the teachers. It also showed that school location significantly influenced the possession and utilization of computer literacy skills by the teachers. These results were discussed and one of the major recommendations was that government should organize in-service training programmes to up-date computer literacy skill of teachers and provide avenue for their utilization.